2015
DOI: 10.1002/dmrr.2533
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients other than carbohydrates: their effects on glucose homeostasis in humans

Abstract: Besides carbohydrates, other nutrients, such as dietary protein and amino acids; the supply of fat, vitamin D, and vitamin K; and sodium intake seem to affect glucose homeostasis. Although their effect is less pronounced than that of the amount and composition of carbohydrates, it seems reasonable to consider how nutrient intake habits may be modified to support an improved glucose homeostasis. For instance, taking into account the effect of some nutrients to lower blood glucose concentration on a day-by-day b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 154 publications
(231 reference statements)
0
18
0
Order By: Relevance
“…25‐OH vitamin D3 has also been implicated in glucose control because of an inverse correlation between plasma levels and impaired glucose tolerance (rev in refs. []). However, supplementing diets with vitamin D with or without calcium produces mixed effects on glucose regulation in healthy individuals or diabetics .…”
Section: Discussionmentioning
confidence: 99%
“…25‐OH vitamin D3 has also been implicated in glucose control because of an inverse correlation between plasma levels and impaired glucose tolerance (rev in refs. []). However, supplementing diets with vitamin D with or without calcium produces mixed effects on glucose regulation in healthy individuals or diabetics .…”
Section: Discussionmentioning
confidence: 99%
“…Few modifiable risk factors for GDM have been identified, but diet has been indicated as one of the most important ones as it is relatively easy to modify [7,8]. Recent reviews have summarized evidence that show there is a relation between diet and the development of glucose intolerance in non-pregnant populations [9][10][11]. Both protective and risk-enhancing associations were observed between different dietary factors and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Other beneficial effects attributed to moderate-high protein diets in the literature are the improvement of glucose homeostasis [80], the possibility of lower blood lipids [81], the reduction of blood pressure [82], the preservation of lean body mass [83] or the lower of cardiometabolic disease risk [84,85]. However, there are other studies that have not found benefits associated to a moderate-high protein diet [76].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…However, there are other studies that have not found benefits associated to a moderate-high protein diet [76]. This fact may be explained by the different type of proteins and their amino acid composition [80], as well as by the different type of populations included in each study [85]. Therefore, more research in the field is needed in order to make these results consistent.…”
Section: Dietary Patternsmentioning
confidence: 99%